Remembering British television audience, archive and industry - Gorton, Kristyn 1972-; Garde-Hansen, Joanne 1975- (Film & media, 2019)
"This original book asks how, in an age of convergence, when 'television' no longer means a box in the corner of the living room that we sit and watch together, do we remember television of the past? How do we gather and archive our memories? Kristyn Gordon and Joanne Garde-Hansen explore these questions through first person interviews with tv producers, curators and archivists, and case studies of popular television series and fan communities such as 'Cold Feet' and 'Doctor Who'. Their discussion takes in museum exhibitions, popular televison nostalgia programming and 'vintage' tv websites"...